The Role of Dynamic Assessment in EFL Writing Class - Lutfi Ashar Mauludin; Triubaida Maya Ardianti (Metathesis: Journal of English Language, Literature, and Teaching, 2017)
Several studies in some countries have mentioned the effectiveness of Dynamic Assessment (DA) in improving the students’ writing skills in English as a Foreign Languge (EFL) context. This study investigates the role of DA in improving students’ writing skill in Indonesian setting. The study used a quasi-experimental method in a public university in Indonesia. The participants were 30 English Diploma Students in their second year. The students were divided into control and experimental group. The experimental group received the treatment using DA approach, meanwhile the control received traditional method. The data were gathered through pretest and posttest. The data then were tabulated using SPSS. The descriptive analysis was conducted to find out its signficance. The result shows that DA has significant role in improving the students’ writing skill. Keywords: Dynamic Assessment, Writing Skills, EFL